«Մշակ» լրագրի գովազդային գործունեությունը (1872–1892 թթ.) - Տարոն Դանիելյան (Հայկական ՍՍՀ գիտությունների ակադեմիա)
Газета «Мшак» («Работник») начала выходить в Тифлисе в период промышленных и социальных реформ, благодаря чему развивается система периодической печати, происходят перестановки на поле рекламной деятельности. В условиях конкуренции издатель-редактор Гр. Арцруни активно оперировал всеми видами и средствами рекламной деятельности, применяемыми отечественными и зарубежными редакциями (полилингвизм сообщений, скидки, бонусные подарки, товарообмен). Реклама обеспечивала «Мшак»-у незначительную дополнительную прибыль; газета существовала исключительно за счет средств издателя. The newspaper “Mshak” (“Worker”) began its publication in Tiflis during the period of industrial and social reforms thanks to which the system of periodical press developed and rearrangements in the field of advertising activity took place. Due to competitive conditions publishing editor Gr. Artsruni actively operated all kinds and means of advertising activity which were exercised by domestic and foreign editorial offices (polylinguism of the notices, discounts, bonus gifts, barters). Advertisement provided slight additional profit for the newspaper “Mshak”: the newspaper existed solely at the expense of the publisher.
Keywords: General Works; Պարբերական; H Social Sciences; HAD Advertising